Alcoholic delirium tremens with hollow viscus perforation scheduled for emergency laparotomy - Anand T Talikoti (Indian Journal of Anaesthesia, 2012)
Alcohol is a drug consumed at some time in life by up to 80% of the population according to western statistics. Wide differences in socioeconomic status in India contribute to various degrees and severity of alcoholism and its associated complications. The symptoms of alcohol withdrawal range from such minor ones as insomnia and tremulousness to severe complications such as withdrawal seizures and delirium tremens. Although alcohol withdrawal syndrome has been reported in the literature in post-operative periods and in Intensive Care Unit, there is paucity of information on treatment and preparation of a patient with alcohol withdrawal syndrome coming for emergency surgical procedures. The surgical stress and deranged liver function in such cases poses an additional challenge to the anaesthesiologist. Here, we report the successful management of a case of acute alcoholic delirium tremens who presented with hollow viscous perforation for emergency exploratory laparotomy.